Doublecortin in Oligodendrocyte Precursor Cells in the Adult Mouse Brain - Boulanger, Jenna J.; Messier, Claude (Frontiers in Neuroscience, 2017)
Oligodendrocyte precursor cells (OPC) are glial cells that differentiate into myelinating oligodendrocytes during embryogenesis and early stages of post-natal life. OPCs continue to divide throughout adulthood and some eventually differentiate into oligodendrocytes in response to demyelinating lesions. There is growing evidence that OPCs are also involved in activity-driven de novo myelination of previously unmyelinated axons and myelin remodelling in adulthood. Considering these roles in the adult brain, OPCs are likely mobile cells that can migrate on some distances before they differentiate into myelinating oligodendrocytes. A number of studies have noted that OPCs express doublecortin (DCX), a microtubule-associated protein expressed in neural precursor cells and in migrating immature neurons. Here we describe the distribution of DCX in OPCs. We found that almost all OPCs express DCX, but the level of expression appears to be much lower than what is found in neural precursor. We found that DCX is downregulated when OPCs start expressing mature oligodendrocyte markers and is absent in myelinating oligodendrocytes. DCX does not appear to signal an immature neuronal phenotype in OPCs in the adult mouse brain. Rather, it could be involved either in cell migration, or as a marker of an immature oligodendroglial cell phenotype.